Process for producing a sintered compact with a color gradient for use in preparing dental restorations, ceramic compact, and use of ceramic compact

By using a variety of matrix powders to prepare ceramic molds with step-by-step tone gradients, the problems of dental ceramic restoration materials in strength, edge strength, light transparency and processability are solved, and the high performance and natural tone gradient of ceramic dental restoration materials are achieved.

JP7649287B2Active Publication Date: 2025-03-19VITA ZAHNFABRIK H RAUTER GMBH & CO KG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022506828
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-08
Filing Date
2020-08-05
Publication Date
2025-03-19
Estimated Expiration
2040-08-05

AI Technical Summary

Technical Problem

Existing dental ceramic restoration materials have difficulty achieving both strength, edge strength, light transparency and processability, especially when creating thin-walled dental restoration materials with natural tone gradients.

Method used

By using a system containing a variety of matrix powders, a ceramic mold specific with a step tone gradient is prepared, and the chemical composition and physical properties of each ceramic powder layer are adjusted to achieve the personalized strength and transparency of the ceramic mold specific.

Benefits of technology

The high edge strength, good light transparency and natural tone gradient of ceramic dental restoration materials are achieved, simplifying the processing process and avoiding the need for manual adjustment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649287000004
    Figure 0007649287000004
  • Figure 0007649287000005
    Figure 0007649287000005
  • Figure 0007649287000001
    Figure 0007649287000001
Patent Text Reader

Abstract

The present invention relates to a process for producing a ceramic compact, comprising the steps of: a) providing three or more ceramic powder layers arranged in layers to form a compacted element; and b) sintering the compacted element obtained in step b to form a ceramic compact, the ceramic powder layers having different compositions, each ceramic powder layer comprising a mixture of at least two different base powders, each base powder comprising at least 80 wt. % ZrO2 and at least 0.02 wt. % Al2O3, each amount based on the total weight of the base powders.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention provides a method for producing ceramic shaped articles, ceramic shaped articles obtainable by the method according to the invention, and their use as dental restorations. [Background technology]

[0002] A wide variety of both organic polymeric and ceramic materials are known for dental restorations. Ceramic materials usually have higher strength but are more difficult to process for the tailor-made production of dental restorations. For ceramic dental restorations, both glass-ceramic and oxide-ceramic materials are available on the market. For the manufacture of dental restorations, glass-ceramic materials usually use fusion processes, while oxide-ceramic materials require pressing and sintering processes using powder technology.

[0003] In the prior art, multilayer blocks for dental CAD-CAM applications made of feldspar or leucite-based ceramics are known. They correspond to the appearance of natural teeth in terms of aesthetics, but usually have strengths in the range of 150 to 200 MPa. However, such strengths are not very suitable for dental restorations, especially with low thicknesses. On the other hand, high strengths can be achieved with layered zirconia blocks. However, they are usually opaque and therefore cannot be used as monolithic dental restorations. Therefore, manual reworking is required to use high-strength zirconia restorations. This may involve infiltrating the porous framework with a colored liquid before sintering or using stained or veneered ceramics to individually color-match the sintered restoration to the natural tooth color. Summary of the Invention [Problem to be solved by the invention]

[0004] A particular challenge in dental restorations is to produce natural color gradations in ceramic restorations, while at the same time high demands are placed on dental restorations with regard to their strength, especially their edge strength, translucency, and workability. [Means for solving the problem]

[0005] Surprisingly, it has been found that the problems presented by the prior art can be solved by the present invention, in particular by using a system comprising several base powders that allows the production of graduated color gradations in ceramic bodies in which both the translucency and the strength of the final product can be individually adjusted. [Brief description of the drawings]

[0006] [Figure 1] FIG. 1 shows an example of a dental restoration obtained from an exemplary ceramic compact. [Diagram 2] FIG. 2 shows an example of a dental restoration obtained from an exemplary ceramic compact. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention relates to a method for producing a sintered compact with color gradation for use in manufacturing dental restorations, comprising the steps of: a) mixing at least three different base powders to prepare a ceramic powder layer mixture; b) stacking the ceramic powder layer mixture obtained in step a) to form at least five different laminated ceramic powder layers; c) pressing the laminated ceramic powder layers to form a compact; and d) sintering the compact obtained in step c) to form a ceramic compact, each ceramic powder layer comprising a mixture of at least three different base powders, each of the base powders comprising at least 80 wt. % ZrO2 and at least 0.02 wt. % Al2O3, each amount based on the total weight of the base powders.

[0008] Preferred embodiments of the invention are found in the dependent claims.

[0009] Within the scope of the present invention, the ceramic powder layer consists of at least three identifiable base powders. In particular, the powder layer preferably consists of three or four identifiable base powders, the ceramic powder layer preferably being in the form of a homogenous mixture of the base powders. The ceramic powder layers are stacked, each adjacent powder layer differing in their chemical composition and / or physical properties. The difference in the composition of the individual powder layers can be achieved by the type and amount of suitable base powders selected. Thus, the ceramic powder layer comprises at least three different base powders. In one embodiment, at least two, preferably at least three, in particular all ceramic powder layers comprise the same base powder, but in different amounts. It has been found that a modular system can be built with a limited number of suitable base powders, which can be used to set the properties of the individual ceramic powder layers, in particular the color, translucency, and physical properties. In addition to the ceramic components, the ceramic powder layers usually contain organic components, such as press additives. However, their proportion is limited and should not exceed 10% by weight based on the ceramic powder layer.

[0010] In a preferred embodiment, the ceramic powder layer or layers, in particular each ceramic powder layer, preferably comprises at least three base powders, preferably four base powders.

[0011] It has proven advantageous to provide four or five ceramic powder layers, each different in terms of their composition. In particular, by using five or more ceramic powder layers, a good color gradient and a gradient of physical properties, which are important for dental restorations, can be realized. Thus, in particular, the cervical part of the artificial tooth, designed with a deeper, darker color, can be adjusted with a gradual transition to the lighter apical and dentin areas of the artificial tooth, so that aesthetic and mechanical requirements can be met.

[0012] In a particularly preferred embodiment, the process according to the invention provides at least five powder layers in step a), each powder layer comprising four different base powders, but each powder layer comprising a different amount of the respective base powder. Surprisingly, it has been found that it may be possible to carry out the work particularly efficiently and cheaply when each ceramic powder layer comprises four or more base powders. The invention therefore further relates to a ceramic powder layer comprising four or more base powders.

[0013] In a preferred embodiment of the invention, each ceramic powder layer of the compact comprises one or more coloring metal oxides. In another embodiment, the concentration of coloring metal oxides is different in each powder layer. Preferably, each intermediate layer, i.e. each powder layer bounded by two directly adjacent powder layers (adjacent layers), is surrounded by adjacent layers that comprise a higher concentration of coloring metal oxide compared to the intermediate layer. Preferably, each intermediate layer is surrounded by adjacent layers that comprise a lower concentration of coloring metal oxide. More preferably, each intermediate layer is surrounded by one adjacent layer with a lower concentration of coloring metal oxide and one adjacent layer with a higher concentration of coloring metal oxide.

[0014] In a preferred embodiment of the invention, the compact comprises powder layers in which, proceeding from the outer powder layer, the concentration of one or more colouring metal oxides increases from layer to layer. In particular, this has the advantage that a step-wise colour gradation can be produced. In another preferred embodiment of the invention, the ceramic powder layer or layers, preferably all powder layers of the compact comprise a colouring metal oxide in an amount of 0.1 to 2.5 wt.-%, more preferably 0.2 to 2.2 wt.-%, in particular 0.2 to 1.5 wt.-%, each amount based on the total weight of the powder layers.

[0015] In a preferred embodiment, the compact comprises powder layers in which proceeding from an outer powder layer, the concentration of at least one colouring metal oxide increases, preferably all the way to the opposing outer layer.

[0016] In a preferred embodiment of the invention, each ceramic powder layer of the compact comprises Fe2O3. In another embodiment, the concentration of Fe2O3 is different in each powder layer. Preferably, each intermediate layer, i.e. each powder layer bounded by two directly adjacent powder layers (adjacent layers), is surrounded by one adjacent layer that comprises a higher concentration of Fe2O3 compared to the intermediate layer. Preferably, each intermediate layer is surrounded by one adjacent layer that comprises a lower concentration of Fe2O3. More preferably, each intermediate layer is surrounded by one adjacent layer with a lower concentration of Fe2O3 and one adjacent layer with a higher concentration of Fe2O3.

[0017] In a preferred embodiment of the invention, the compact comprises powder layers in which the concentration of Fe2O3 increases from layer to layer, proceeding from the outer powder layer. In particular, this has the advantage that a step-wise color gradation can be created. In another preferred embodiment of the invention, one or more ceramic powder layers of the compact, preferably all powder layers, comprise Fe2O3 in an amount of 0.01 to 0.25 wt.-%, more preferably 0.02 to 0.2 wt.-%, in particular 0.1 to 0.18 wt.-%, each amount based on the total weight of the powder layers.

[0018] In a preferred embodiment of the invention, each ceramic powder layer of the compact comprises Er2O3. In another embodiment, the concentration of Er2O3 is different in each powder layer. Preferably, each intermediate layer, i.e. each powder layer bounded by two directly adjacent powder layers (adjacent layers), is surrounded by one adjacent layer that comprises a higher concentration of Er2O3 compared to the intermediate layer. Preferably, each intermediate layer is surrounded by one adjacent layer that comprises a lower concentration of Er2O3. More preferably, each intermediate layer is surrounded by one adjacent layer that comprises a lower concentration of Er2O3 and one adjacent layer that comprises a higher concentration of Er2O3.

[0019] In a preferred embodiment of the invention, the compact comprises powder layers in which the concentration of Er2O3 increases from layer to layer, proceeding from the outer powder layer. In particular, this has the advantage that a step-wise color gradation can be created. In another preferred embodiment of the invention, one or more ceramic powder layers of the compact, preferably all powder layers, comprise Er2O3 in an amount of 0.01 to 1.5 wt.-%, more preferably 0.05 to 1.2 wt.-%, in particular 0.1 to 0.9 wt.-%, or 0.2 to 0.5 wt.-%, each amount based on the total weight of the powder layers.

[0020] In another preferred embodiment, one or more, preferably each, powder layer of the compact comprises Co3O4. Typically, the amount of Co3O4 may be in the range of 0.001 to 0.01, more preferably 0.002 to 0.08 wt.-%, in particular 0.003 to 0.006 wt.-%, based on the total weight of the powder layer.

[0021] Each of the base powders of the invention comprises at least 80% by weight ZrO2 and at least 0.02% by weight Al2O3, each amount based on the total weight of said base powder. In a preferred embodiment of the invention, the base powder comprises 0.02 to 0.6% by weight, more preferably 0.03 to 0.4% by weight, in particular 0.04 to 0.2, or 0.003 to 0.1, or 0.02 to 0.08% by weight Al2O3, the amount being based on the total weight of said base powder. The base powders are suitable for the manufacture of dental restorations, so that they meet the requirements of biocompatibility even in the sintered state. The high proportion of zirconia, preferably stabilized by yttria, further increases the strength of the final sintered ceramic. The base powders are selected to match each other in terms of grain size and sintering behavior, so that no sintering voids occur during sintering. The mixture of base powders allows to achieve individual coloration and translucency in each ceramic powder layer, which is selected to result in a continuous and stepwise color gradation, if there are adjacent powder layers.

[0022] The presence of yttria or erbium oxide is beneficial for phase stabilization of zirconia-based ceramics in the sintered state.

[0023] In a preferred embodiment, at least one of the base powders, preferably at least two or three, in particular all base powders, comprises yttria (Y2O3) and / or erbium oxide (Er2O3), preferably in an amount of at least 3 wt.-%, in particular at least 5 wt.-%, or at least 6 wt.-%, in particular from 4.5 to 11 wt.-%, in particular from 6 to 10 wt.-%, based on the total weight of the components of the base powder.

[0024] In one embodiment of the present invention, at least one, preferably at least two or at least three of the base powders contain a coloring metal oxide. For example, these coloring metal oxides may be selected from the group consisting of iron oxide (Fe2O3), cobalt oxide (Co3O4), erbium oxide (Er2O3). By adding these coloring metal oxides, individual tooth colors can be created. By mixing several base powders in each ceramic powder layer, a defined and balanced material can be obtained.

[0025] In an embodiment of the invention, at least one of the base powders, preferably at least two or at least three of the base powders, comprises zirconia, optionally together with hafnia, in an amount of at least 89 wt.-%, preferably from 89 to 98 wt.-%, in particular from 90 to 96 wt.-%, each amount being based on the total weight of the components of the base powder.

[0026] In one embodiment, the base powder may comprise zirconia (HfO2) and hafnia (HfO2), preferably in a weight ratio of ZrO2 to HfO2 of 25:1 to 98:1, particularly 30:1 to 90:1, and especially 50:1 to 90:1.

[0027] In a preferred embodiment, the powder layer includes a base powder A including 92 to 96 wt. % zirconia, 0.02 to 0.1 wt. % alumina, 5 to 9.5 wt. % yttria, and 0.02 to 0.1 wt. % cobalt oxide, each amount being based on the total weight of the base powder A.

[0028] In another preferred embodiment, the powder layer comprises a base powder B including 85 to 93 wt. % zirconia, 0.02 to 0.1 wt. % alumina, and 7.5 to 11 wt. % erbium oxide, each amount being based on the total weight of the base powder B.

[0029] In another embodiment, the powder layer comprises a base powder C comprising 90 to 94 wt. % zirconia, 0.02 to 0.1 wt. % alumina, and 5.5 to 8.0 wt. %, preferably 6.5 to 9.5 wt. %, yttria, each amount being based on the total weight of the base powder C.

[0030] In another preferred embodiment of the present invention, the powder layer comprises a base powder D comprising 90 to 94 wt. % zirconia, 0.02 to 0.1 wt. % alumina, 5.5 to 8.0 wt. %, preferably 6.5 to 9.5 wt. % yttria, and 0.1 to 0.3 wt. % iron oxide, each amount being based on the total weight of the base powder D.

[0031] In another embodiment of the present invention, at least one base powder, preferably all base powders, further comprises an organic component, preferably in an amount of 3 to 6% by weight, in particular 4 to 5% by weight. Suitable organic components include in particular binders and press additives that can be easily removed thermally in the debinding process. Binders suitable for zirconia sintered powders are known to those skilled in the art. These include, for example, polyvinyl alcohol (PVA).

[0032] Preferably, the base powder has a density of 1.2 g / cm 3 It has a bulk density of less than 1000 nm.

[0033] It has proven advantageous to use a base powder with a mean particle size D50 of 35 μm to 85 μm, preferably 40 μm to 80 μm, in particular 50 μm to 70 μm or 40 to 60 μm. The granular powder is measured in the dry state by laser diffraction using a Cilas particle size distribution analyzer.

[0034] Typically, the particle size D50 of the base powder after removal of the inorganic components, i.e. organic components such as binders, is 0.1 to 1 μm, preferably 0.2 to 0.8 μm, in particular 0.2 to 0.7 μm, as measured by laser diffraction. It has been found that the particle size makes a positive contribution to sintering, in particular to the color gradient between the individual powder layers.

[0035] In a particularly preferred embodiment of the invention, it can be obtained by stacking five ceramic powder layers in step b). The stacking of the layers can be carried out, for example, in a cylindrical container to form a disk. Usually, uniaxial pressing of the powder layers can be carried out after the application of each layer. This can be done, for example, using a pressing plunger, which merely causes a preliminary compression. The uniaxial pressing of the layers perpendicular to the layer surface is preferably carried out under a pressure of 10 to 20 MPA, in particular 12 to 15 MPa.

[0036] More preferably, the pressing in step c) is first performed by uniaxial pressing perpendicular to the layer surface, preferably at 2.8 g / cm 3 and preferably has a density of 2.5 to 2.75 g / cm 3 Density in the range of, for example, 2.65 g / cm 3 The uniaxial pre-compression results in a better and more intimate mix and therefore potentially a more uniform transition between the layers.

[0037] In a further embodiment of the process of the present invention, the pressing in step c) is carried out isostatically, said isostatic pressing preferably following a uniaxial pre-compression, and having a density of 3.4 g / cm 3Less than 2.80 to 3.15 g / cm 3 , specifically 2.85 to 3.10 g / cm 3 The isostatic pressing is preferably carried out after all layers of the compact have been stacked. Suitable pressures for the isostatic pressing are typically in the range of 500 to 10000 bar, preferably in the range of 800 to 8000 bar, for example in the range of 1000 to 7000 bar, or in the range of 1000 to 3000 bar.

[0038] The thickness of the individual powder layers of the compact may differ. In a preferred embodiment, at least two of the ceramic powder layers differ in terms of thickness. Preferably, at least two of the ceramic powder layers of the compact have a thickness difference of at least 5%. Typically, the compact may be in the form of a cylindrical circular disk having a diameter in the range of 50 to 200 mm, for example in the range of 75 to 150 mm. The total thickness of the cylindrical disk may be, for example, in the range of 8 to 40 mm, preferably in the range of 10 to 30 mm, in particular in the range of 13 to 25 mm. The dimensions refer to the compact in the green state.

[0039] With regard to color design and subsequent processing, it has proven to be advantageous if at least one, preferably both, of the outer ceramic powder layers of the compact is thicker than the ceramic powder layers in between. In particular, when the ceramic compact produced according to the invention is used for the production of dental restorations, such a layer structure comprising at least one thicker outer layer has proven to be advantageous, since this is a structure suitable for processing with CAD / CAM systems or other subtractive processing methods.

[0040] In a particularly preferred embodiment of the present invention, in step b) of the present invention five ceramic powder layers are deposited, the first powder layer being 20 to 30%, preferably 22 to 28%, the second powder layer being 10 to 20%, preferably 12 to 18%, the third powder layer being 15 to 25%, preferably 17 to 23%, the fourth powder layer being 10 to 20%, preferably 12 to 18%, and the fifth powder layer being 20 to 30%, preferably 22 to 28%, of the total thickness of the stacked powder layers, totalling 100%.

[0041] In another embodiment of the present invention, the sintering of step d) of the present invention is carried out at a temperature in the range of 950 to 1100°C, preferably at a temperature of 980 to 1050°C, to form a pre-sintered ceramic compact (body-in-white). Typically, sintering is carried out for a time sufficient to remove the existing binder and provide the compact with sufficient strength for subtractive processing. The pre-sintered and separated compact is called a "body-in-white". The density of the body-in-white is preferably 3.15 to 3.35 g / cm. 3 in the range of 3.2 to 3.3 g / cm 3 These density ranges have proven to be particularly advantageous in terms of high edge stability and low tool wear.

[0042] In one embodiment, the sintering to form the body-in-white of step d) of the process of the invention is for more than 30 minutes, preferably more than 1 hour, in particular more than 20 hours or more than 50 hours, for example from 60 to 200 hours, or from 70 to 150 hours.

[0043] In particular, for producing a ceramic dental restoration, it is expedient that the pre-sintered ceramic green body in step d) is treated by a subtractive process, preferably followed by final sintering in a separate step. When applying subtractive processes, the sintering shrinkage is usually taken into account in the calculations.

[0044] Surprisingly, it has been found that the optimum setting of surface hardness can be achieved in the bond layer structure by using the process according to the present invention.Therefore, the apical part of dental restoration can be set to a lower hardness, for example, compared to the cervical part.In a preferred embodiment of the present invention, the Vickers hardness of one outer layer is different from that of the opposite outer layer.Preferably, the difference in Vickers hardness is at least 5%, more preferably at least 10%, in particular at least 15%, or at least 20%, respectively, based on the outer layer with lower hardness.

[0045] Preferably, the Vickers hardness [HV2] according to DIN EN 843 of the outer layer having the lower hardness is between 45 and 60, more preferably between 50 and 59. Preferably, the Vickers hardness [HV2] according to DIN EN 843 of the outer layer having the higher hardness is above 60, in particular in the range from 61 to 80, more preferably in the range from 65 to 75.

[0046] Final sintering is usually carried out at a temperature above 1350°C, preferably above 1400°C, in particular in the range of 1420°C to 1600°C or 1450°C to 1550°C.

[0047] The sintering time for the final sintering is usually 4 minutes or more, preferably 5 minutes or more, and particularly within the range of 5 to 120 minutes.

[0048] The invention further relates to a ceramic shaped article obtainable by the method according to the invention.

[0049] The ceramic moldings according to the present invention can be used in particular in the dental field.They are characterized by high edge strength, excellent structure and high three-point bending strength of dental restorations.Therefore, the ceramic moldings according to the present invention are preferably dental restorations such as inlays, onlays, crowns, bridges, veneers or abutments for implants.

[0050] The invention further relates to the use of the ceramic molded body according to the invention for a dental restoration or for producing a dental restoration. EXAMPLES

[0051] Table 1 shows the four base powders A to D used in the composition of the ceramic powder layer. The particle size D50 of the base powders is in the range of 40 to 80 μm. The particle size D50 of the inorganic components of the base powders is in the range of 0.2 to 0.7 μm.

[0052] Each amount given is based on the total weight of the powder composition.

[0053] [Table 1]

[0054] The layer arrangement shown in Table 2 below indicates the composition of the individual ceramic powder layers in the compact. Since the compact is provided for use in the manufacture of dental restorations, the composition of the layers is designed according to the tooth position. The composition of the powder layers is formed from the base powders by changing the ratios to obtain an ideal color gradation. The composition of each powder layer is achieved by homogeneously mixing the stated amounts of base powders. The powders are subsequently arranged layer by layer in a cylindrical mold with a diameter of 100 mm, and the layer thickness is set to 18 mm. The powder layers are pre-compressed uniaxially under a pressure of 13 MPA perpendicular to the layer surface and then isostatically compressed under a pressure of 2000 bar.

[0055] Debonding then takes place at about 1000° C. for about 100 hours. The body-in-white thus obtained is milled into a dental restoration using a CAD / CAM system.

[0056] These pre-sintered and treated bodies-in-white are then subjected to final sintering at 1450° C. for 120 minutes.

[0057] [Table 2]

[0058] In this example, the ceramic powder layers comprise 25% of the total thickness of the compact with Layer 1 (tip), 15% with Layer 2 (dentin / tip), 20% with Layer 3 (dentin), 15% with Layer 4 (dentin / neck), and 25% with Layer 5 (neck).

[0059] 1 and 2 show examples of dental restorations obtained from exemplary ceramic compacts.

[0060] Layer and color transitions are fluid. Restorations show excellent edge strength and stability. No recoloring or realignment of teeth is required.

[0061] An optimal structure and composition of the layer exhibits substantially uniform shrinkage during sintering throughout the layer, which is advantageous for perfectly fitting fabrication of dental restorations, particularly since laborious reworking can be substantially avoided.

[0062] Surprisingly, it has been found that the hardness of the ceramic can be optimally set by the layer structure. The Vickers hardness of the exemplary disk is measured on the upper side (light layer, tip) and on the lower side (dark layer, neck) after firing in a kiln. For the exemplary embodiment, the density of the white body, and therefore the Vickers hardness, is always greater on the lower side than on the upper side.

[0063] The following Table 3 shows the determined values ​​of Vickers hardness [HV2] according to DIN EN 843. [Table 3]

Claims

1. 1. A process for producing a sintered compact with a color gradation for use in preparing a dental restoration, comprising: a) mixing four different base powders to prepare a ceramic powder layer mixture; b) stacking the ceramic powder layer mixture obtained in step a) to form a laminated ceramic powder layer including at least five distinct ceramic powder layers; c) pressing the laminated ceramic powder layers to form a compact; d) sintering the compact obtained in step c) to form a ceramic compact; at least three of said ceramic powder layers each include a mixture of four different base powders in different amounts; The base powders each contain at least 80% by weight of ZrO 2 and at least 0.02 wt. % Al 2 O 3 and each amount is based on the total weight of the base powder. The ceramic powder layer is composed of 92 to 96 wt. % zirconia, 0.02 to 0.1 wt. % Al. 2 O 3 , 3.5 to 6.5 wt.% Y 2 O 3 %, and 0.02 to 0.1 wt. % Co 3 O 4 The amount of each of the base powders is based on the total weight of the base powder A. The ceramic powder layer is comprised of 85 to 93 wt. % zirconia, 0.02 to 0.1 wt. % Al. 2 O 3 and 7.5 to 11.0 wt.% Er 2 O 3 The amount of each of the base powders B is based on the total weight of the base powder B. The ceramic powder layer is composed of 90 to 94 wt. % zirconia, 0.02 to 0.1 wt. % Al. 2 O 3 and 5.5 to 8.0 wt. % Y 2 O 3 The amount of each of the base powders C is based on the total weight of the base powder C. The ceramic powder layer is composed of 90 to 94 wt. % zirconia, 0.02 to 0.1 wt. % Al. 2 O 3 and 5.5 to 8.0 wt. % Y 2 O 3 , 0.1 to 0.3 wt.% Fe 2 O 3 wherein the amounts of each are based on the total weight of base powder D.

2. All of the base powders are 2 O 3 and / or Er 2 O 3 2. The process of claim 1, wherein the base powder comprises at least 6% to 10% by weight of the total components of the base powder.

3. 10. The process of claim 1, wherein three of the base powders include a coloring metal oxide.

4. 2. The process of claim 1, wherein three of the base powders contain zirconia and hafnium oxide at between 90% and 96% by weight, each amount being based on the total weight of the base powder components.

5. 2. The process of claim 1, wherein at least two of the ceramic powder layers have different thicknesses, the difference being at least 5% when the thickness of the laminated ceramic powder layer is taken as 100%.

6. 2. The process of claim 1, wherein at least one outer ceramic powder layer is thicker than the ceramic powder layer between both outer ceramic powder layers.

7. 2. The process according to claim 1, characterized in that the ceramic compact pre-sintered in d) is treated by a subtractive method, followed by final sintering in a separate step.

8. 2. The process according to claim 1, characterized in that the base powder has an average particle size D50 of 40 μm to 60 μm.

9. 2. The process of claim 1, wherein the inorganic component of the base powder has an average particle size D50 of 0.2 to 0.7 μm as measured by laser diffraction.

10. Fe 2 O 3 The concentration of Fe increases from layer to layer proceeding from the outer powder layer, and all powder layers contain between 0.1 and 0.18 wt.% Fe. 2 O 3 10. The process of claim 1, further comprising:

11. A ceramic formed body obtainable by the process according to any one of claims 1 to 10.

12. Use of the ceramic molding according to claim 11 for a dental restoration.

Citation Information

Patent Citations

  • Gradient transparent zirconium oxide dental ceramic and preparation method thereof

    CN103058655B

  • Multiple-oxide-doped gradient-color zirconia dental prosthesis and preparation method thereof

    CN104844200A

  • Manufacturing process for a non-dense sintered ceramic molded body having at least two layers

    JP2015518460A

  • Ceramics blank for multilayer-structure dental cutting processing having high color tone reproducibility

    JP2017185163A

  • Functional zirconia block with various colors and transmitting properties

    KR101324467B1